Kinerja Karyawan: Peran Kualitas Sumber Daya Manusia, Lingkungan Kerja, dan Budaya Organisasi - Maria Rosvita Hoar; Ignatius Soni Kurniawan; Jajuk Herawati (Universitas Batanghari, 2021)
This study aims to examine the effect of the quality of human resources, work environment, and organizational culture on employee performance. The sampling technique used a saturated sample, with as many as 50 employees at Kantor Pusat Waroeng Spesial Sambal Yogyakarta. Primary data was taken by using a questionnaire. Data were analyzed using multiple linear regression analysis. The results showed that the quality of human resources, work environment, and organizational culture had a positive and significant effect on employee performance. The implication directs the leadership to maintain or improve the implementation of the antecedent variables of employee performance.